A NH4F interface passivation strategy to produce air-processed high-performance planar perovskite solar cells. (20th August 2018) - Ren, Ziqiu; Wang, Na; Zhu, Menghua; Li, Xin; Qi, Jingyao
Abstract: The simple assembling process and lower manufacturing cost are crucial for wide application of perovskite solar cells. In this work, we report an efficient interface passivation strategy for preparing high-performance planar perovskite solar cells, which does not require well-controlled moisture and oxygen atmosphere. A NH4 F solution-based additive is introduced to passivated TiO2 electron transfer layer, which offers reduction of oxygen-induced defects and residual surface hydroxyl groups, and lower trap state level. Using a typical planar structure of FTO/NH4 F-TiO2 /CH3 NH3 PbI3 /Spiro-OMeTAD/Au, the champion device achieves a power conversion efficiency of 15.61%. After 28-day durability test, the device with NH4 F-treated TiO2 storing in air without any encapsulation exhibits a little efficiency loss (<10%). Our work demonstrates a generic approach to develop air-processed efficient planar perovskite solar cells by interface engineering for future commercialization. Graphical abstract: Image 1 Highlights: A NH4 F additive is introduced to passivated TiO2 electron transfer layer. The oxygen-induced defects and residual hydroxyls at interface are suppressed. The air-processed device achieves a power conversion efficiency of 15.61%. The NH4 F-treated device storing in air exhibits a little efficiency loss.